Dynamic analysis of blockage behavior of fine particles in a packed bed by discrete element method. (9th August 2021) - She, Xuefeng; Liu, Songhao; Liu, Yanjun; Zhao, Wenshu; Wang, Yanjiang; Zhou, Heng
ABSTRACT: The dynamic blockage behaviour of fine particles in a packed bed was simulated using the discrete element method (DEM). The influence of key variables are examined. The calculation results showed that fine particles blockage in packed bed are easy to occur in the area where fine particles just enter the bed. The mechanism of blockage formation is mainly due to mechanical interactions between fine particles, which can create arches on packed bed and stop the flow. When the fine particles form a bridge across the pore throat of the orifice, the bottleneck of void space becomes the starting point for blockage formation. The fine particles with a larger rolling friction coefficient have a higher clogging ratio. With the increase in charging fine particles, the fine particles experience more collisions with each other, and the clogging ratio increases. The initial velocity of fine particles also has an impact on the blockage behaviour.